REFLEKSI NILAI-NILAI SPIRITUAL PERSPEKTIF ISLAM:DEKONSTRUKSI MENTAL AKUNTAN - Hasbullah Hajar (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2023)
The current challenge for an accountant is to understand that accountants are not only required to know and comply with the professional code of ethics, but accountants are also required to understand the socio-spiritual accountants. If accountant was understanded about them socio-spiritual, eventually they will made spiritual values as a principle in carrying out his job. This research try to explore spiritual values, especially in the religion perspective, namely Islam. In exploring spiritual values, I found that the potential for spiritual values contained in the holy book of the Koran which is reflected in the nature and character of the Prophet Muhammad S.A.W, then this potention are probably to change the mind and mentality of accountants who have been confined by capitalism. This paper ends with the idea that a quality of a Muslim's spiritual will determine the good implementation and depth of internalization of Islamic spiritual values in carrying out his job.